Viscous phase-field modeling for chemo-mechanical microstructural evolution: application to geomaterials and pressure solution. (15th December 2020) - Guével, A.; Rattez, H.; Veveakis, E.
Abstract: The microstructural geometry of materials has a significant influence on their macroscopic response, especially when the process is essentially microscopic as for chemo-mechanical processes. In this work, we are pursuing the idea that interface-tracking models like phase-field modeling can capture the microstructural dynamics and enrich macroscopic constitutive laws for geomaterials. We are introducing a phase-field theory for chemo-mechanical processes derived from fully-dissipative thermodynamics, enabling the inclusion of dissipative effects such as the evolution of the microstructural curvature. The resulting microstructural viscosity introduces rate-dependency through the associated relaxation time. To emphasize the influence of irregular microstructural geometries, we study numerically the chemo-mechanical response of digitalized geomaterials at the grain scale under pressure solution creep. We show that tracking the grain boundary evolution allows for capturing the microscopic transient nature of pressure solution. Our numerical results are discussed against experimental results from the literature and the properties of macroscopic creep laws are shown to be linked to the evolution of the microstructure.